Profesi Keguruan Dalam Pembelajaran di Sekolah Dasar - Adelia Fitri; Aidatul Fauziah; Aulia Sari Damanik; Era Yunita; Dina Oktapia; Syahpan Ramadhan (Jurnal Ilmiah Wahana Pendidikan, 2022)
The teaching profession is an activity that shows and upholds the principles and principles of professionalism in carrying out its duties and obligations in educating and teaching students. Teacher is a strategic profession for the empowerment of a nation. Teachers have a code of ethics for the teaching profession which aims to uphold the dignity of the profession. The main mission of a teacher is an effort to educate the nation's life in all its aspects, both spiritual, emotional, intellectual, and physical. Teachers are required to strengthen the character of students who internalize the main values of strengthening character education (CAR), namely religiosity, nationalism, independence, mutual cooperation and integrity in every learning. To face the era of technological advancements that demand student literacy skills, a curriculum that integrates six basic literacy skills is needed, namely literacy, digital, numeric, financial, science, culture and citizenship. Efforts to improve the quality of education in Indonesia are always carried out through efforts to prepare professional teachers through a quality and accountable teacher education system.